Tradisi Sesaji Rewanda Dalam Perspektif Sakralitas dan Profanitas Emile Durkheim - Reny Setiyowati; Luthfi Rahman; Novi Lieana Anggraeni (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This study aims to elucidate the proportional relationship between Islam and Javanese culture through the analysis of the Rewanda offering tradition in Semarang. Utilizing Emile Durkheim's theory of the sacred and the profane as the analytical framework, this research identifies and classifies the elements of the Rewanda tradition into two main categories: sacred and profane. The study employs a descriptive qualitative method through observation, interviews, and literature review. Firstly, the research reveals the sacred elements within the Rewanda offering tradition, which include religious rituals, ancestor worship, and spiritual symbolism that reinforce Islamic values within the context of Javanese culture. These elements demonstrate that the tradition functions not only as a means of worship but also as a medium for strengthening spiritual and social bonds within the community. Secondly, the study classifies the profane elements of the tradition, encompassing aspects of daily life and social interactions related to the practice of the tradition. These profane elements reflect cultural adaptation and social interactions accompanying the ritual, showing how the tradition integrates with the everyday life of the Semarang community. The theoretical implications of this research offer a deeper understanding of how the Rewanda tradition merges sacred and profane elements and highlights its role as a bridge between religion and culture. This study enriches the literature on the relationship between religion and culture and provides valuable insights into the dynamics of local traditions in preserving cultural heritage and spiritual values in contemporary society.